Analisis SWOT untuk Meningkatkan Daya Saing pada UMKM Tarekli Salama Kelurahan Na’e Kota Bima - Kartin Aprianti; Irma Mardian; Sendarina Sendarina; Nur Afni; Sri Rahma; Putri Sulistiani Juary; Aldy Bima Prasetya; M. Dhani Inzaghi; Andika Putra Bayu (Journal of Management and Social Sciences, 2024)
This research discusses efforts to increase the competitiveness of "Tarekli" MSMEs through SWOT analysis. The main goal of this analysis is to maximize strengths and opportunities, while reducing weaknesses and threats faced by the business. The research method uses a descriptive qualitative approach, relying on data from scientific journals and online publications. The analysis results show that Tarekli has advantages in the form of product and service quality, but faces challenges such as distribution difficulties and dependence on raw materials with unstable prices. Innovation in packaging and brand strengthening were identified as strategic steps to increase competitiveness. SWOT analysis provides important insights for MSMEs in formulating growth strategies and increasing customer satisfaction..